Aplicação eletroanalítica de complexos oxo-manganês biomimetizadores de centros ativos enzimáticos na determinação de espécies de interesse analítico - Machini, Wesley Bruno da Silva [UNESP] (2015)
Multinucleate manganese complexes have gained notoriety due its ability to mimic the mechanism of oxygen evolution complex of photosystem II, besides the great catalytic importance with processes of electronic transfer of multistage. These properties of multinucleated complexes make them interesting to study the electrochemical processes in modified electrodes for applications such as chemical sensors. In this way, this dissertation aimed to synthesize and characterize oxo-manganese complexes containing different ligands ([MnIV(μ-O)(salpn)]2 and [MnIII/IV(μ-O)(phen)2]2(ClO4)3) looking for structural, kinetic and catalytic characteristics similar to biomimicking complexes of enzymatic active center for subsequent electroanalytical application in the development of biomimetic sensors and determining species of analytical interest. First, studies with oxo-manganese-Schiff complex [MnIV(μ-O)(salpn)]2 is given through the synthesis of the Salpn ligand and then of the complex. These in turn were characterized with efficiency by scanning electron microscopy, UV-Vis spectrophotometry, infrared spectroscopy and luminescence. Different electrochemical techniques were used to investigate and qualitatively understand the electrochemical behavior of [MnIV(μ-O)(salpn)]2 complex in solution. The construction of a modified electrode based on [MnIV(μ-O)(salpn)]2-Nafion®/Pt was performed, however, the electrochemical studies were not promising, due to loss of analytical signal as consequence of the low solubility of complex in the immobilizing step. Finally, the electrocatalytic and biomimicking activity of [MnIV(μ-O)(salpn)]2 complex in solution compared to the reduction of hydrogen peroxide could successfully be investigated providing promising results in biomimicking enzymatic active centers of the Mn-containing catalase enzyme. The oxo-manganese-phenanthroline complex [MnIII/IV(μ-O)(phen)2]2(ClO4)3 was ...